2020
DOI: 10.1155/2020/6316921
|View full text |Cite
|
Sign up to set email alerts
|

Synovitis, Acne, Pustulosis, Hyperostosis, and Osteitis Syndrome with Purely Osteolytic, Not Osteosclerotic, Lesions Mimicking a Malignant Tumor

Abstract: Synovitis, acne, pustulosis, hyperostosis, and osteitis (SAPHO) syndrome is a rare inflammatory disorder with multiple phenotypes. The syndrome has identifiable radiologic characteristics that are the most important when making a diagnosis. X-rays of cases diagnosed with SAPHO syndrome reveal sclerotic lesions or mixed lytic and sclerotic lesions. Pure osteolytic lesions in SAPHO syndrome are rare, and to the best of our knowledge, no study has reported the radiologic change of purely osteolytic lesions to ost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Imaging findings are also consistent with this process: early radiological findings are osteolytic lesions, and late radiological features are usually osteoproliferative 16 . Kinoshita et al 17 reported a case of left femur involvement in SAPHO syndrome with the radiologic change from osteolytic lesions to osteosclerotic lesions over time confirmed. However, further clinical observation is needed if the sclerosing changes of the dura mater occur in the late stage of SAPHO syndrome due to hypertrophic meningitis caused by cranial bone involvement.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Imaging findings are also consistent with this process: early radiological findings are osteolytic lesions, and late radiological features are usually osteoproliferative 16 . Kinoshita et al 17 reported a case of left femur involvement in SAPHO syndrome with the radiologic change from osteolytic lesions to osteosclerotic lesions over time confirmed. However, further clinical observation is needed if the sclerosing changes of the dura mater occur in the late stage of SAPHO syndrome due to hypertrophic meningitis caused by cranial bone involvement.…”
Section: Discussionmentioning
confidence: 79%
“…15 Imaging findings are also consistent with this process: early radiological findings are osteolytic lesions, and late radiological features are usually osteoproliferative. 16 Kinoshita et al 17 reported a case of left femur involvement in SAPHO syndrome with the radiologic change from osteolytic lesions to osteosclerotic lesions over time confirmed.…”
Section: Discussionmentioning
confidence: 90%
“…This may suggest that our patient's infection was slightly more chronic than his symptoms initially suggested. Chronic inflammation of the SC joint can also be seen in conditions such as SAPHO syndrome, and several case reports have described this condition in children 7 . In addition, C. acnes is theorized to trigger an autoimmune chronic inflammatory state in patients with SAPHO syndrome 8 .…”
Section: Discussionmentioning
confidence: 99%